Recent advances in active agent-filled wrapping film for preserving and enhancing the quality of fresh produce - Rozman, Azri Shahir; Hashim, Norhashila; Maringgal, Bernard; Abdan, Khalina; Sabarudin, Akhmad (Elsevier, 2023)
Along with the increased demand for fresh produce, the production of non-degradable plastics or packaging has simultaneously increased. Increasing awareness and knowledge of the harmful effects of non-degradable products has increased the development of biodegradable and environmentally friendly packaging film for fresh produce. This review article emphasizes and summarise the concept and characteristics of active agent-filled wrapping film as an emerging technology for preserving the quality of fresh produce. Further, the effects of active agent-filled wrapping film regarding fresh produce quality together with the consumer acceptance view are critically discussed. The future direction of this wrapping film technology is also highlighted. The importance of understanding the concept of active agent-filled wrapping film is elucidated and the uniqueness of it is emphasized especially the concept of antioxidant and antimicrobial properties. These advancements in wrapping film technology offer advantages to not only sustainable fresh produce industries but also promote eco-friendly practices.